A Review on Unstructured Data Processing in Hybrid Cloud Platform - Rajassekharan, Dinesh (Journal of Soft Computing Paradigm, 2022)
Cloud storage systems are widely employed in many applications due to their improvement in cost, storage availability and security. Hybrid cloud platform refers to the architecture of a cloud system that combines more than one computing environments at a time. It can be either with one public and one private platform or the combination of two private or two public platforms. The hybrid cloud platform has the ability to share the information among the connected systems and that can be processed parallelly while accessing the data. The data that are stored in cloud platforms are mostly in unstructured format that could not be used for any applications like prediction, recommendation, and estimations. This paper reviews the attainments of the previous works that were used for data distribution and partitioning in a hybrid cloud platform, by ensuring the privacy and security of the stored data. The work also explores the future directions on the unstructured data processing by summarizing the research issues observed from the review analysis.
Keywords: Cloud architecture; load analysis; resource allocation; data filtering; cloud modelling